REKONDISI MESIN GERINDA CUTTER - vergo banarma; Putra perdana guna darma; Ariyanto Ariyanto; Tuparjono Tuparjono (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
US-350 cutter grinding machine is one of machines in workshop of Politeknik Manufaktur Negeri Bangka Belitung and functions to make and sharpen cutters. Up and down sled doesn’t move so the cutting isn’t optimal. Vacuum cleaner hose is broken so vacuum cleaner can't work. One way to restore function of damaged component is by reconditioning US-350 cutter grinding machine. Goal of final project is restore condition of US-350 cutter grinding machine to an acceptable condition based on user's standard operating. Final project carried out is to recondition US-350 cutter grinding machine by making threaded boshings, replacing flat belts and timing belts, modifying idler belts, making vacuum cleaners, replacing broken vacuum cleaner hoses and replacing motor bearings. Testing final project is done by testing vibration using vibroport, testing engine geometry using dial indicator, testing each component function and testing accuracy. Test results show condition of cutter grinding machine has functioned well to operating conditions can be accepted by operating user. Condition in question is sledding of engine head has moved, vacuum cleaner system has been able to suck dust, electric motor has been functioning properly and isn’t noisy based on results of testing function of bearing according to user operating standards.